Premature Ovarian Insufficiency - diagnostic and therapeutic challenges - Izabela Hawranik; Mikołaj Tomasik; Paweł Warzyszak; Róża Małek; Maria Milczek; Wojciech Żołyniak; Szymon Niski; Ziemowit Żaba; Aleksandra Lisowska; Mateusz Skrzypek (Nicolaus Copernicus University in Toruń, 2023)
Introduction and purpose: Premature Ovarian Insufficiency (POI) is a rare but serious disease diagnosed in about 1% of women before the age of 40. It is characterized by hypoestrogenism and an increase in the level of the follicle-stimulating hormone, which is associated with menstrual disorders, pregnancy failures and a reduced quality of life. The main causes of POI include a genetic background and autoimmune abnormalities, as well as increasingly jatrogenic factors. Care for patients is focused on hormone replacement therapy and infertility treatment. The aim of this review is to discuss current treatment methods, the impact of early diagnosis and the prevention of premature ovarian insufficiency, which affects the ability to have one's own offspring. The article also describes new methods of infertility treatment that are under investigation. Materials and methods: This literature review is based on articles published in the PubMed database from 2015 to 2022 using the following phrases: premature ovarian insufficiency, premature ovarian insufficiency stem cells State of knowledge: The only way to treat infertility in women with POI is egg donation. Currently, research is being conducted to achieve early diagnosis, introduce new treatment methods and reduce the number of iatrogenic forms of POI. Conclusion: The main problem for women diagnosed with POI is the difficulty or often impossibility of having their own children. Egg donation does not allow for the transfer of the patient's genetic material, and is also not available as a treatment option in some countries. For this reason, new methods for early diagnosis, treatment, and prevention of POI are being developed.